2017
DOI: 10.1016/j.nicl.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological and clinical effects of fNIRS-controlled rTMS in patients with panic disorder/agoraphobia during cognitive-behavioural therapy

Abstract: BackgroundA relevant proportion of patients with panic disorder (PD) does not improve even though they receive state of the art treatment for anxiety disorders such as cognitive-behavioural therapy (CBT). At the same time, it is known, that from a neurobiological point of view, PD patients are often characterised by prefrontal hypoactivation. Intermittent Theta Burst Stimulation (iTBS) is a non-invasive type of neurostimulation which can modulate cortical activity and thus has the potential to normalise prefro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…To our knowledge, this is the first study that investigates the neuronal correlates of PP in a simultaneous fNIRS-EEG study. First of all, our results showed that the paradigm used induced a phobic reaction consistent with reactions reported in the literature with increased subjective distress, avoidance 10 , 15 , 16 , 56 , heart rate 36 and EMG-measured facial expressions 6 , 57 , 58 , indicating that videos are realistic enough to elicit a fear response in PP. Our results with respect to ERPs are well in line with the existing literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, this is the first study that investigates the neuronal correlates of PP in a simultaneous fNIRS-EEG study. First of all, our results showed that the paradigm used induced a phobic reaction consistent with reactions reported in the literature with increased subjective distress, avoidance 10 , 15 , 16 , 56 , heart rate 36 and EMG-measured facial expressions 6 , 57 , 58 , indicating that videos are realistic enough to elicit a fear response in PP. Our results with respect to ERPs are well in line with the existing literature.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were observed with respect to fNIRS. For example, Deppermann et al reported increased functional connectivity between prefrontal areas in spider phobic patients (PP) during an emotional stroop task 15 , 16 . Additionally, Landowska et al 17 aimed to measure brain activity using virtual reality in participants with moderate acrophobia.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent Theta Burst Stimulation (iTBS), a new rTMS technique, was tested in the study from Deppermann et al [13] iTBS or sham were applied over the left DLPFC in 15 daily sessions for 3 weeks, as an augmentation of a 9-week CBT protocol. No significant differences were found in the main outcome measures in the comparison between iTBS and sham stimulation, still the iTBS group showed a superior improvement on the agoraphobic avoidance scores compared to the sham condition.…”
Section: Resultsmentioning
confidence: 99%
“…Also, receiving a total of 8 weeks (phase 1 plus phase 2) (40 trains) of rTMS proved to be more effective than the 4-week treatment (20 trains) [15]. In the other rTMS trial [13], with 15 trains (3 weeks) of iTBS over de left DLPFC, the active condition was not superior to the sham condition. In a study published in 2007 [24], treatment-resistant PD patients received 10 trains of low-frequency rTMS in the right DLPFC, but active stimulation was not superior to sham stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were conducted using repetitive transcranial magnetic stimulation (rTMS) along with cognitive and additional emotional Stroop tasks, and the results associated with PFC activations/deactivations were compared with those of healthy persons. 155,156 At the baseline (without rTMS), the fNIRS measurements associated with the VFT revealed hypofrontality in the dorsolateral PFC, in panic disorder patients, which signi¯cantly di®ered from the activations observed in healthy persons. However, after sham rTMS, a signi¯cant increase in activation was reported in the left inferior frontal gyrus.…”
Section: Verbal°uency Taskmentioning
confidence: 98%